A Sparse Matrix Fast Transpose Algorithm Based on Pseudo-Address - Da, Wenjiao; Ren, Zhiguo; Lu, Jiao; Shi, Xuxia (2019 International Conference on Intelligent Computing, Automation and Systems (ICICAS), 2019)
Sparse matrix is a kind of special matrix which is often studied by computer scientists, and computer scientists mainly study its storage structure and algorithm. In this paper, we conceive and design the three-tuple compression storage structure of sparse matrix and the pseudo-address compression storage structure, discuss the transpose algorithm of irregular sparse matrix, mainly study the fast transpose algorithm of sparse matrix, and propose a new matrix transpose algorithm on it for the first time-the sparse matrix fast transpose algorithm of pseudo-address storage structure. It is hoped that this conclusion will provide general algorithm for industrial control and data compression researchers.